Modeling analysis and fabrication of MEMS capacitive differential pressure sensor for altimeter application. (3rd April 2018) - Parthasarathy, Eswaran; Malarvizhi, S.
Abstract: This paper proposes the modeling analysis of MEMS highly sensitive Capacitive Differential Pressure Sensor (CDPS) and also the development of a fabrication process for CDPS structures for aircraft altimeter applications. Highly sensitive CDPS structure models using circular and square sandwich polyimide diaphragm membranes, with and without center boss, were adopted, whereas other studies report on silicon diaphragms. CDPS characterization was carried out to analyze the deflection sensitivity, capacitive sensitivity, stress on diaphragm membrane and the effect of temperature on capacitive sensitivity. Simulation results of square diaphragm without center boss show better characteristics than other proposed diaphragm structures. This design yields 145.8 nm/mbar and 0.574 fF/mbar of deflection and capacitive sensitivity, respectively. The maximum stress developed on the diaphragm at maximum working pressure is less than the yield stress of polyimide material by a factor of 1.77 and capacitive sensitivity deviates at ±0.00195%/°C. From the modeling analysis, square diaphragm CDPS structure yields better characteristics and hence the fabrication process for CDPS has been developed, and its fabrication process flow verified using Intellisuit virtual fab tool.